Antibacterial effects of tomato ethanol extract (Solanum lycopersicum L.) against S. mutans and P. gingivalis: a laboratory experiment - Rahmawati, Dicha Yuliadewi; Kurniawan, Viola Febi; Sanjaya, Oei Tirza Cintya; Sugiaman, Vinna Kurniawati; Mandalas, Henry Yonatan (Universitas Padjadjaran, 2023)
ABSTRACT Introduction: Process of dental plaque formation consists of three stages, pellicle formation, initial colonization facultative gram-positive one of microbes is S. mutans, secondary colonization and microbial maturation by Porphyromonas intermedia, P. gingivalis, Fusobacterium nucleatum. Formation of dental biofilm is considered to be main etiology of chronic periodontitis. Bacteria that often involved in chronic periodontitis are P. gingivalis. Tomatoes (Solanum lycopersicum L.) content lycopene compounds, flavonoids, and saponins have been shown to inhibit or kill bacterial growth. The aim is to analyze the antibacterial effect of servo tomato ethanol extract against S. mutans and P. gingivalis. Methods: This research was a laboratory experimental one with a posttest only control group design where observed variable diameter of the inhibition zone was produced from ethanolic extract of tomato (Solanum lycopersicum L.) in various concentrations of 3.125, 6.25, 12.5, 25, 50 and 100% chlorhexidine 0.2% as a positive control, negative control of distilled water against S. mutans and P. gingivalis on blood agar media. The method used in this study was the well-diffusion test. Results: The highest inhibitory zone at 100% concentration with a diameter of 32.10 mm was very strong; lowest inhibition at 3.123% was 3.95 mm, weak classification and against P. gingivalis at 3.125%, it was 3.72 mm, weak classification, meanwhile at 100% concentration, it was 9.67 mm, medium classification. The results of the One Way ANOVA statistical test showed a p<0.05 which had a significant effect in inhibiting the growth of S. mutans and P. gingivalis. Conclusions: There was an antibacterial effect of the ethanolic extract of tomato against S.mutans produced a larger diameter and stronger inhibition zone meanwhile against P.gingivalis produce medium inhibition zone. The content of tomatoes such as lycopene compounds, flavonoids, and saponins have been shown to inhibit or kill bacterial growth.Keyword : tomato ethanol extract (Solanum lycopersicum L.), S. mutans, P. gingivalis, antibacterial